Some American views on penology - Buchanan, Walter J. (Statistical and Social Inquiry Society of Ireland, 1923)
I have the honour this evening to lay before you some considerations on certain aspects of prison reform and "penology," which I had the opportunity of examining when engaged as a Member of the recent Indian Prisons Commission, which in 1919-20 went round the world for the purpose of studying the prison systems of other countries with a view to their application, as far as may be, to India.
Read December 15th, 1921
Keywords: Penal system; Juvenile criminals; 314.15